PEMANFAATAN TEKNOLOGI PENGINDERAAN JAUH DAN SIG UNTUK EVALUASI LAHAN KERING DI KABUPATEN BANTAENG, SULAWESI SELATAN - , ARTHUR GANI KOTO, S.TP, Prof. Dr. Totok Gunawan, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dry land is a land that was never flooded or under water in a small part of the year, which consists of dry land lowland and upland plateau. Dry land generally located at mountainous region characterized by undulating topography and a receiving area, and impregnation rainwater which is then channeled to the lowlands, either through the soil surface (river) as well as through a network groundwater earth. Dry land agriculture is the largest foreign exchange earner in Bantaeng Regency. This study aims to : (1) analyzing the spatial distribution of dry land using remote sensing and GIS technology in Bantaeng Regency, (2) analyzing dry land regions utilizing remote sensing technology and GIS in Bantaeng Regency. Digital image processing techniques used is the composite image color, contrast stretching, supervised classification Support Vector Machines (SVM) method and slope classification. Method in this study is a combination of digital analysis of Landsat 5 TM using supervised classification SVM based on knowledge based classification with the results of field work and spectral reflectance Landsat 5 TM were processed using Geographic Information System (GIS) in the making of maps the physical characteristics of the land (landform, slope, and present land use). Inhibiting factors dry land of the land capability is soil type, soil texture, soil depth, rock abundance, threats flooding, organic content, soil erosion and slope. Each of these factors inhibitors, unless the slope, interpreted manually from Landsat 5 TM and ASTER GDEM 2 images. Method of determining the dry land acquired based on the analysis of rainfall, land capability and present land use. The area of dry land spreading in the subdistrict of Gantarangkeke, Tompobulu, Eremerasa, Bantaeng and Uluere which total area covered is 20.643,986 ha and non upland areas are in the subdistrict of Pajukukang, Bantaeng, Bissappu and Eremerasa which total area covered is 19.119,146 ha. The results of analysis show that the spreading in the dominant upland areas with heavy normal rainfall with the land capability II-IV and the present land use in the domination mixed farms and farmland.